Nilai-Nilai Akhlak dalam Novel Lost In Ningxia: Assalamu’alaikum Beijing 2 Karya Asma Nadia - Fajar Abrar Maulana (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Morality is a fundamental aspect of human life, related to the good and bad of a person's behavior. Morality is also the embodiment of the perfection of one's faith when viewed from a religious perspective. Conceptually, morality is understood as a state of the soul that provides a strong drive, resulting in a variety of spontaneous actions. This research aims to analyze the moral values (akhlak) in the novel Lost in Ningxia: Assalamu’alaikum Beijing 2 by Asma Nadia. The study employs a qualitative approach using content analysis techniques. Data were collected through dialogue excerpts, narratives, and character actions, which were then classified into three categories: divine morality, individual human morality, and social human morality. The results indicate that these three moral values are integrally present throughout the plot. Divine morality is reflected through attitudes of sincerity (ikhlas), love, hope, and gratitude toward Allah. Individual human morality is evidenced by traits of modesty and optimism. Meanwhile, social human morality emerged as the most dominant category, demonstrated through compassion, honesty, and devotion to parents. This research is expected to contribute to literary studies by highlighting the dominance of social morality as a primary moral construct in contemporary Islamic novels.